2019
DOI: 10.1080/24748706.2019.1634854
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Reduction in Hospitalization Costs Associated with Next-Day Discharge following Transfemoral Transcatheter Aortic Valve Replacement in the United States

Abstract: Background: Index hospital costs for transcatheter aortic valve replacement (TAVR) remain high. Next-day discharge (NDD) is a safe and feasible strategy in select patients. We sought to explore cost savings associated with NDD TAVR. Methods: We conducted a retrospective observation cohort study of all fee-for-service Medicare beneficiaries who underwent elective, uncomplicated, transfemoral TAVR in 2016. We employed a cross-sectional regression analysis to estimate risk-adjusted hospital costs savings of NDD r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 37 publications
0
15
0
1
Order By: Relevance
“… 25 The goal is to leverage current evidence, to reduce the disruptions to patients’ health status and physiological reserves during their admission and to decrease the intensity of health services requirements to enhance access to TAVI. 26 The adoption of a minimalist approach as the preferred default strategy is an imperative to promote access to care in the ‘new normal’ as COVID-19 continues to dictate priorities of care.…”
Section: The Imperative Of a Minimalist Approachmentioning
confidence: 99%
“… 25 The goal is to leverage current evidence, to reduce the disruptions to patients’ health status and physiological reserves during their admission and to decrease the intensity of health services requirements to enhance access to TAVI. 26 The adoption of a minimalist approach as the preferred default strategy is an imperative to promote access to care in the ‘new normal’ as COVID-19 continues to dictate priorities of care.…”
Section: The Imperative Of a Minimalist Approachmentioning
confidence: 99%
“…The latest Canadian data indicated a median LOS of 2 for TF-TAVI in 2017/2018 in Quebec while a recent evaluation of the Vancouver 3M (Multidisciplinary, Multimodality, But Minimalist) clinical pathway (26) found that 80% of patients could be discharged after 1 day while 90% could be discharged within two days. In addition to improving outcomes, these changes to processes of care and health service utilization are associated with significant cost savings (29). This evolution of TAVI as a mature minimally invasive treatment option will continue to narrow the gap with more invasive approaches, and is projected to become economically dominant by providing greater quality-adjusted life expectancy and lower long-term costs than SAVR (30).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to improving outcomes, these changes to processes of care and health service utilization are associated with significant cost savings. 29 This evolution of TAVI as a mature, minimally invasive treatment option will continue to narrow the gap with more-invasive approaches, and it is projected to become economically dominant by providing greater quality-adjusted life expectancy and lower long-term costs than SAVR. 30 Future research is warranted to determine if the change in technology and practice associated with TF-TAVI will result in decreased costs and improved outcomes associated with AS hospitalizations in Canada.…”
Section: Discussionmentioning
confidence: 99%
“…They found 14.7% of TAVR patients were discharged the day after their procedure, 35.1% on postoperative day 2, and 14.8% after 5 or more days. 8 Next-day discharge was associated with a cost savings of $4,507 per patient compared with discharge on postoperative day 2 and $7,499 compared with all-comers.…”
Section: The Economics Of Transcatheter Aortic Valvementioning
confidence: 94%